No evidence of age-related decline in propagated acer pseudoplatanus and Fraxinus excelsior plants - Zheng, Tong; Mencuccini, Maurizio; Abdul Hamid, Hazandy (Wiley, 2023)
Although a substantial body of evidence suggests that large and old trees have reduced metabolic levels, the search for the causes behind this observation has proved elusive. The strong coupling between age and size, commonly encountered in the field, precludes the isolation of the potential causes. We used standard propagation techniques (grafting and air‐layering) to decouple the effects of size from those of age in affecting leaf structure, biochemistry and physiology of two broadleaved trees, Acer pseudoplatanus (a diffuse‐porous species) and Fraxinus excelsior (a ring‐porous species). The first year after establishment of the propagated plants, some of the measurements suggested the presence of age‐related declines in metabolism, while other measurements either did not show any difference or suggested variability across treatments not associated with either age or size. During the second year after establishment, only one of the measured properties (specific leaf area) continued to show some evidence of an age‐mediated decline (although much reduced compared to the field), whereas, for some properties (particularly for F. excelsior ), even the opposite trend of age‐related increases was apparent. We concluded that (1) our plants suffered from grafting shock during year 1 and they gradually recovered during year 2; (2) the results over 2 years do not support the statement that age directly mediates ageing in either species but instead suggest that size directly mediates ageing processes; and (3) neither shoots nor roots of A. pseudoplatanus showed any evidence of senescence.